2020
DOI: 10.1021/acs.macromol.0c01361
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Decisive Structural Parameters for the Self-Assembly of Supramolecular Polymer Bottlebrushes Based on Benzene Trisureas

Abstract: By introducing strong directed hydrogen bonds to an amphiphilic polymer, we demonstrate that phase transitions from spherical to cylindrical morphologies in aqueous solutions can significantly be shifted to favor the assembly of supramolecular polymer bottlebrushes. In water, a forced self-assembly of polymers into cylindrical structures remains a challenge as the often required hydrophobic shielding induces forces, which tend to minimize the surface area. The herein presented novel benzene trisureas can overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 58 publications
4
40
0
Order By: Relevance
“…33 A strategy to circumvent statistical reactions and to introduce one different side arms onto the core is to start from a C 2symmetrical core. [34][35][36][37][38][39][40][41] The group of Bouteiller synthesized Nsubstituted benzene-1-urea-3,5-biscarboxamide (BUBA) monomers with a significantly enhanced yield, starting from a commercially available dimethyl 5-aminoisophthalate core. 42 The BUBA molecules showed cooperative self-assembly into long helices in organic media, similar to BTAs.…”
Section: Introductionmentioning
confidence: 99%
“…33 A strategy to circumvent statistical reactions and to introduce one different side arms onto the core is to start from a C 2symmetrical core. [34][35][36][37][38][39][40][41] The group of Bouteiller synthesized Nsubstituted benzene-1-urea-3,5-biscarboxamide (BUBA) monomers with a significantly enhanced yield, starting from a commercially available dimethyl 5-aminoisophthalate core. 42 The BUBA molecules showed cooperative self-assembly into long helices in organic media, similar to BTAs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12–27 ] Considering the latter, we have previously shown that the number of H‐bonds per central motif, and thus the interaction strength, is decisive to obtain SPBs. [ 28–30 ] However, next to the strength of the supramolecular interaction and the main axial assembly, a lateral assembly appears to be crucial for the formation of cylindrical structures, which is similarly observed for other of the above‐mentioned motifs.…”
Section: Methodsmentioning
confidence: 81%
“…Compounds 1a–c were further studied via sedimentation velocity experiments in the AUC to resolve apparent distributions of the sedimentation coefficients, s (Figure 1B). [ 28,29,33 ] For all three compounds, roughly monomodal distributions of s were observed with signal (weight) average sedimentation coefficients of s = 1.0 S ( 1a ), s = 2.4 S ( 1b ), and s = 3.3 S ( 1c ). The very small s ‐value for 1a is in accordance with the SAXS and cryoTEM results indicate the presence of unimers next to small aggregates.…”
Section: Methodsmentioning
confidence: 95%
“…The general structure of the tested BTP and BTU is depicted in Figure 1 [ 19 20 ]. While the hydrogen bonding moieties are either urea-based or peptide-based (i.e., phenylalanine) units, the dodecyl chains act as hydrophobic shields to induce the amphiphilic assembly in water and prevent the surrounding water from interfering with the hydrogen bonds in the interior [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…An alternative is the use of molecular motifs capable of forming directional supramolecular interaction forces, such as hydrogen bonds or π-interactions, to guide the one-dimensional (1D) assembly of established, commercial polymers in solution [17]. We recently reported the self-assembly of polyethylene oxide (PEO) polymers into cylindrical nanostructures, also called supramolecular polymer bottlebrushes (SPBs), based on the end group modification with hydrogen bond forming benzenetrisurea (BTU) and benzenetrispeptide (BTP) motifs [18][19][20]. The resulting amphiphilic character of the materials facilitated a control of the kinetic assembly, which provided access to stable nanostructures on a broad length range (<100 nm-2 µm).…”
Section: Introductionmentioning
confidence: 99%